2012
DOI: 10.1007/s00424-012-1136-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TRPV1 and TRPV4 channels in migration of rat pulmonary arterial smooth muscle cells

Abstract: Pulmonary hypertension, the main disease of the pulmonary circulation, is characterized by an increase in pulmonary vascular resistance, involving proliferation and migration of pulmonary arterial smooth muscle cells (PASMC). However, cellular and molecular mechanisms underlying these phenomena remain to be identified. In the present study, we thus investigated in rat intrapulmonary arteries (1) the expression and the functional activity of TRPV1 and TRPV4, (2) the PASMC migration triggered by these TRPV chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 37 publications
3
60
0
Order By: Relevance
“…1A). Preincubation of PA rings with 5 M HC-067047, a concentration used previously on PASMCs (6,47), for 15 min caused significant reduction in the maximal response (E max ϭ 63.0 Ϯ 7.6, n ϭ 10, P Ͻ 0.01) and the pD 2 (7.2 Ϯ 0.08, P Ͻ 0.01) of PE ( Fig. 1, A-C).…”
Section: Evaluation Of Trpv4 Antagonists For the Study Of Pulmonary Vmentioning
confidence: 72%
See 2 more Smart Citations
“…1A). Preincubation of PA rings with 5 M HC-067047, a concentration used previously on PASMCs (6,47), for 15 min caused significant reduction in the maximal response (E max ϭ 63.0 Ϯ 7.6, n ϭ 10, P Ͻ 0.01) and the pD 2 (7.2 Ϯ 0.08, P Ͻ 0.01) of PE ( Fig. 1, A-C).…”
Section: Evaluation Of Trpv4 Antagonists For the Study Of Pulmonary Vmentioning
confidence: 72%
“…Hence, the participation of TRPV4 in CHPH is solely restricted to pulmonary vasculature and is independent of cardiac function. Recent evidence from others also shows that CH enhances TRPV4-induced Ca 2ϩ release from ryanodine-sensitive Ca 2ϩ stores in rat PASMCs (6) and activation of TRPV4 promotes PASMC migration (47). Taking all these pieces of information together, we postulate that TRPV4 in PASMCs contributes to the development of CHPH through multifaceted influences on Ca 2ϩ influx and release, promoting basal and myogenic tone, cell migration, and vascular reactivity to collectively muster an elevation of pulmonary vascular resistance and vascular remodeling.…”
Section: -Ht (M)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that TRPV4 channels are expressed on vascular endothelial and smooth muscle cells in a variety of blood vessels and that activation of these channels induces vascular smooth muscle hyperpolarization, the release of NO from the endothelium, and vasodilation (2,5,9,11,12,25). It has been hypothesized that TRPV4 channel activation represents the hyperpolarizing mechanism by which ACh induces endothelium-dependent vasodilation (7,16,17,27).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary artery smooth muscle cells also express TRPV1 and TRPV4. TRPV1 and TRPV4 agonists (capsaicin and 4a-PDD, respectively) induced migratory responses in these cells in a manner that was inhibited by both capsazepine (a first-generation TRPV1 antagonist) (Wang et al, 2008a) and the TRPV4 blocker HC-067047 (Martin et al, 2012).…”
Section: Transient Receptor Potential Channels In Cardiovascular Dmentioning
confidence: 99%